Nilai-Nilai Pendidikan Dalam Kajian Harta Waris dan Wasiat - Sri Wahyuni; Indah Ramadhany; Wismanto Wismanto; Aliza Aliza; Annisa Damai Yanti Samoeri (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
In Islamic law, the division of the estate (faraidh) is part of the problem is already clear rules (qat'i al-dilalah). However, there are still a few people who questioned aspects of justice in this faraidh problem. One solution to bridge this is the concept of testament. The division of property by testamentary relatively more flexible than those specified in the science faraidh. However, will still not be separated from the legal rules that have been set Qur'an and Sunnah